Mapping energy use portfolios and household outcomes in Pakistan: Insights from farm and household surveys in Rahim Yar Khan - Sufian, Farha; Alvi, Muzna; Raja, Sehrish (International Food Policy Research Institute, 2024)
Rural energy access remains a critical challenge in developing economies, with profound implications for agricultural productivity, household welfare, and gender dynamics. Pakistan's economy depends heavily on agriculture, which accounts for 20 percent of its gross domestic product and employs 42 percent of workers. Most farmers are small landholders who struggle with limited energy access and unreliable irrigation. Rain-dependent farming leaves these farmers vulnerable to weather changes, hindering their ability to improve agricultural productivity and resilience through modern agricultural technology. Furthermore, in Pakistan limited access to energy within the household and reliance on traditional cooking methods not only constrain productivity but also directly affect dietary quality for families, especially in low-income and agrarian communities. Women, who traditionally manage household nutrition and often bear the burden of energy-intensive food preparation, are particularly vulnerable to these energy constraints. This policy note examines the rural energy portfolio in Rahim Yar Khan (RYK), in the Punjab province of Pakistan, and its association with household well-being outcomes. The energy portfolio in rural RYK is diverse, with households relying on a combination of traditional and modern sources of energy. This analysis aims to explore how on- and off-farm energy choices impact key aspects of household well-being, including women’s dietary diversity, agency in energy choices, and workload. The findings offer valuable insights for policymakers seeking to promote sustainable energy solutions that enhance household welfare in rural Pakistan.